Effect of partial root zone drying in fruit crops (Indian Journal of Arid Horticulture, 2020)
Partial root zone drying (PRZD) is an advancement over traditional irrigation system. It is the process of irrigating the surface area of the plant sequentially one side after another side. In agriculture where 83 per cent of the total available water is used, adoption of such kind of technique is sure to curtail the requirement of water which is getting scarce day by day. PRZD in fruit crops can reduce irrigation water requirement up to 50 per cent and increase WUE to the extent of 90 per cent. Its usefulness has been proven in grapes, orange, pomegranate and apple. Having gone through literature, it vividly appeared that PRZD technique is worth adoption in view of better WUE. It has all merit of higher yield and quality per unit water consumed. Thus, it is environment friendly too which is much concerned in current day agriculture/horticulture production.
Keywords: Deficit irrigation; fruit quality; PRZD mechanism; regulated deficit irrigation; WU